2019
DOI: 10.3233/ppr-180121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an individualised physical rehabilitation intervention enhanced by progressive muscular relaxation and visualisation exercises on psycho-emotional state in women after breast cancer surgery

Abstract: PURPOSE: Present study aimed to determine the effects of muscular relaxation and visualisation exercises on psycho-emotional state in women after breast cancer surgery during a 4-week individualised intervention. METHODS: The sample size of 51 women was chosen to perform the investigation. Women had undergone surgical treatment (radical mastectomy by Madden) for breast cancer. Participants reported anxiety and depression using the Hospital Anxiety and Depression Scale at baseline, and 4-week post-intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As a result of recent research, it was found that breast cancer survivors had a deterioration in the psycho-emotional status and a decrease in most criteria of quality of life, which were directly related to the severity of post-mastectomy edema, pain, and neurological disorders. 3-6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of recent research, it was found that breast cancer survivors had a deterioration in the psycho-emotional status and a decrease in most criteria of quality of life, which were directly related to the severity of post-mastectomy edema, pain, and neurological disorders. 3-6…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As a result of recent research, it was found that breast cancer survivors had a deterioration in the psycho-emotional status and a decrease in most criteria of quality of life, which were directly related to the severity of post-mastectomy edema, pain, and neurological disorders. [3][4][5][6] Women with breast cancer have an increased risk of developing depression, anxiety, sexual dysfunction, sleep disturbances, cognitive problems, fatigue, and sexual problems. Assessment of life quality parameters has become a significant criterion of woman's cancer rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…141 Thus, the benefits of yoga for people with metastatic cancer and intervention duration in people with localized or regionally advanced cancer requires further study. Hypnosis RCT 9 Anxiety [39][40][41][42][43][44][45] Anxiety and depression 46,47 Mindfulness-based interventions SR 7 Anxiety and depression [48][49][50][51][52][53][54] RCT 7 Depression 55,56 Anxiety and depression [57][58][59][60][61] Music therapy and music-based interventions SR 4 Anxiety and depression [62][63][64][65] RCT 4 Anxiety [66][67][68] Reflexology RCT 9 Anxiety [69][70][71][72] Anxiety and depression [73][74][75][76][77] Relaxation techniques SR 4 Anxiety and depression [78][79][80][81] RCT 5 Anxiety and depression [82][83]…”
Section: Recommendationsmentioning
confidence: 99%
“…Five other RCTs not included in any of the SRs assessed relaxation in 53 women with gynecologic cancers postsurgically 82 ; 51 women after breast cancer surgery 83 ; 52 people in Iran with mixed cancer diagnoses undergoing active treatment 84 ; 81 people undergoing chemotherapy assigned to either biofeedback or relaxation therapy 85 ; and 66 women with gynecologic or breast cancer receiving brachytherapy. 86 Recommendation 1.5.…”
Section: Recommendationsmentioning
confidence: 99%
“…Physical activity is increasingly recognized as an effective method of reducing emotional distress and improving life quality among patients who survived cancer. A growing body of research indicates the benefits of yoga exercises [8][9][10][11][12][13][14], cognitive behavioural therapy [15], mindfulness-based stress reduction [16,17], physical activity [18], music therapy [19,20], progressive muscular relaxation [21][22], and mixed aerobic and muscle strengthening exercise [23] for improving mental and physical conditions in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%